(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1928)
An urn found at Fence’s Farm, Hunterstone contained cremated human bone, charcoal and a bead of shale or lignite. A second urn found at Seamill in 1830 contained cremated human bone. A stone cist found at Phantassie contained the very poorly preserved skeleton of a child.